Functionality and Acceptance of the EsoCap System-A Novel Film-Based Drug Delivery Technology: Results of an In Vivo Study - Christoph Rosenbaum; Michael Grimm; Julius Krause; Adrian Rump; Rebecca Kessler; Norbert Hosten; Werner Weitschies (MDPI AG, 2021)
There are no methods for specific local application of active substances to the mucosa of the esophagus to treat eosinophilic esophagitis or other esophageal diseases. This publication describes the principal in vivo functionality and acceptance of a novel modular drug delivery concept, called EsoCap system, by 12 healthy volunteers. For the first time, the EsoCap system enables targeted placement on the esophageal mucosa of a mucoadhesive polymer film. Acceptance was determined by means of a standardized questionnaire after administration and functionality of the device by MRI scans. Two different setups of the EsoCap system were tested: one setup with a density of 0.4 g/cm3 and one with a density of 1.0 g/cm3. Acceptability of the dosage form was also confirmed in addition to functionality, by measuring the applied film length. It was found that acceptance of the variant with the higher density was significantly better. This novel drug delivery technology could enable a targeted, local and long-lasting therapy of the esophagus for the first time, depending on the polymer film used.